UNOCCUPIED ELECTRONIC STATES IN THE BAND-STRUCTURE OF NIAL(110) - Fauster, Thomas; et al. (Physical Review B, 1992)
The unoccupied electronic states of the clean NiAl(110) surface have been studied with angle-resolved inverse photoemission along the GAMMA-BAR XBAR and GAMMA-BAR YBAR directions of the surface Brillouin zone. The use of a rotatable electron gun allows an independent variation of the incidence angle of the electrons and the exit angle of the photons. Measurements of the photon-emission characteristic of the dipole transitions observed in inverse photoemission can be used to determine the symmetry of the electronic states. For normal incidence of the electron beam, transitions along the GAMMA-M line of the bulk Brillouin zone are detected and the results are compared to band-structure calculations available for the high-symmetry lines.